Wnt5a Promotes Cortical Neuron Survival by Inhibiting Cell-Cycle Activation - Zhou, Li; Chen, Di; Huang, Xu-Ming; Long, Fei; Cai, Hua; Yao, Wen-Xia; Chen, Zhong-Cheng; Liao, Zhi-Jian; Deng, Zhe-Zhi; Tan, Sha; Shan, Yi-Long; Cai, Wei; et al. (Frontiers in Cellular Neuroscience, 2017)
β-Amyloid protein (Aβ) is thought to cause neuronal loss in Alzheimer’s disease (AD). Aβ treatment promotes the re-activation of a mitotic cycle and induces rapid apoptotic death of neurons. However, the signaling pathways mediating cell-cycle activation during neuron apoptosis have not been determined. We find that Wnt5a acts as a mediator of cortical neuron survival, and Aβ42 promotes cortical neuron apoptosis by downregulation the expression of Wnt5a. Cell-cycle activation is mediated by the reduced inhibitory effect of Wnt5a in Aβ42 treated cortical neurons. Furthermore, Wnt5a signals through the non-canonical Wnt/Ca2+ pathway to suppress cyclin D1 expression and negatively regulate neuronal cell-cycle activation in a cell-autonomous manner. Together, aberrantly downregulation of Wnt5a signaling is a crucial step during Aβ42 induced cortical neuron apoptosis and might contribute to AD-related neurodegeneration.